Accelerated Partial Breast Irradiation: Frequent non-professional Phagocytosis in Patients with early, Hormone Receptor-positive Breast Cancer is associated with good Survival - Bauer, Marcus; Schnellhardt, S.; Rosahl, M. -C; Erber, Ramona; Ott, Oliver; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Evaluation of antihyperalgesic and analgesic effects of 35% nitrous oxide when combined with remifentanil A randomised phase 1 trial in volunteers - Wehrfritz, Andreas; Bauer, Marcus; Noel, Nathalie; Ramirez-Gil, Juan Fernando; Ihmsen, Harald; Prottengeier, Johannes; Schüttler, Jürgen; Bessiere, Baptiste (European Journal of Anaesthesiology, 2021)
BACKGROUND Remifentanil is an effective drug in peri-operative pain therapy, but it can also induce and aggravate hyperalgesia. Supplemental administration of N2O may help to reduce remifentanil-induced hyperalgesia.
CRIS-Team WoS Importer:2022-03-04